The Moderation Of Intellectual Capital And Information Asymmetry In The Effect Of Voluntary Reporting On Stock Return - Wardatul Jannah; Erwin Saraswati; Abdul Ghofar (Universitas Muhammadiyah Malang, 2021)
Abstract Voluntary reporting and intellectual capital are important instruments for the provision of information to investors. The information increases investment interest and ultimately affects stock return. This study examines the effect of voluntary reporting on stock return with the moderation of intellectual capital and information asymmetry. The sample of this study is 225 observations from 45 financial and banking companies listed on the Indonesia Stock Exchange during the period of 2015-2019. Financial and banking sector has an important role for companies in other sectors in providing capital and a sense of security for their assets. Multiple regression method and MRA applied in this study have come to findings that voluntary reporting increases stock return, that intellectual capital strengthens the relationship between voluntary reporting and stock return, and that information asymmetry has no effect on the relationship between voluntary reporting and stock return as companies begin to respond to the importance of voluntary reporting to reduce information asymmetry.